Methotrexate in management of Morbidly Adherent Placenta at Latifa Hospital, DHA, Dubai, UAE.: Case report - Fazari, Atif BE; Aristondo, Maria Eugenia Ramirez; Azim, Faiqa; AlMaamari, Basma Abdo; Eltayeb, Rasha (Clinical Journal of Obstetrics and Gynecology, 2019)
Morbidly adherent placenta (MAP) includes the spectrum of placenta accreta, increta, and percreta. It is a major cause of obstetric hemorrhage. Caesarean section is main risk factor for MAP. Ultrasound scan is highly sensitive method for MAP diagnosis and sometime Magnetic resonance image is of choice. Early diagnosis timed elective planned intervention after preparation under skillful multidisciplinary team improve the outcome and minimize the morbidity. Caesarean hysterectomy, major arteries ligation, arteries embolization and leave the placenta in-situ all are choices of management. Use of Methotrexate for the placenta in-situ in MAP is still debatable. We present a case of MAP in which placenta left in- situ followed by multiple Methotrexate injection during postpartum with good outcome and acceptability.